DNA barcoding and integrative taxonomy of Macrobiotus hufelandi C.A.S. Schultze 1834, the first tardigrade species to be described, and some related species - Bertolani, Roberto; Rebecchi, Lorena; Giovannini, Ilaria; Cesari, Michele (Zootaxa, 2011)
Within the framework of a DNA barcoding project on tardigrade species, a study was carried out on Macrobiotus hufelandi C.A.S. Schultze 1834, the first formally described tardigrade species. We used samples collected from the type locality and additional material from other European sites containing species of the “M. hufelandi group”. The study was performed by integrating morphological, karyological and molecular (mt-DNA cox1) information and comparing these data with morphological data from the type material. Several species from this group were found in the type locality of M. hufelandi (near Freiburg, Black Forest, Germany) and these were all barcoded. One was M. hufelandi, the other two were: Macrobiotus sandrae Bertolani & Rebecchi 1993 (originally described from the same locality), and Macrobiotus vladimiri Bertolani, Biserov, Rebecchi & Cesari in press (type locality Andalo, Italy), all with interspecific genetic distances of more than 19%. A fourth cryptic species, which had the same morphology as M. hufelandi but a genetic distance of 6.7%, was not described as a new taxon but named M. cf. hufelandi sp.1 for this study. Macrobiotus sandrae and M. vladimiri were also present (and barcoded) in Italy (Alps). Additional individuals (animals and eggs) were also found, and barcoded, in Italy (Apennines) and Switzerland that belonged to the haplogroup Macrobiotus cf. hufelandi sp. 1. These data together with other recent studies on tardigrade DNA barcoding represent a starting point for further studies on tardigrade biogeography, phylogeography and diversity.